Field screening of linseed genotypes against alternaria blight (Alternaria lini) - Subedi, Subash; Neupane, Saraswati; Yadav, Sailendra; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2023)
Linseed (Linum usitatissimum L.) is a promising but underexplored oilseed crop in Nepal, with considerable expansion potential. However, it faces a significant threat from leaf blight disease, caused by Alternaria lini resulting in notable yield reductions. This study aimed to identify genetic sources of resistance to this pathogen. Fourty-two linseed genotypes, including resistant check ACC#7622 and susceptible check Sarlahi local, underwent disease resistance screening over two years (2021-2022) in field disease screening nurseries at the Oilseed Research Program, Sarlahi, using an incomplete block design. Each block contained seven genotypes, replicated twice. Disease severity, yield and yield attributing traits were assessed. Significant variations in disease and yield traits were observed among the genotypes over the years. While only 19% showed moderate resistance with minimal symptoms compared to susceptible types. None were immune and resistance, with 13 genotypes (31%) classified as moderately susceptible, 26% susceptible and 24% highly susceptible. A significant negative correlation (P≤0.05) between disease severity and grain yield was evident. Genotypes ACC#(5-ICLI-2001-5), ACC#96-001, ACC#7622, ACC#96-004, TN#04, ACC#(9-ICLI-2001-9), ACC#(1-ICLI-2001-1), and TN#08 demonstrated both high yield and moderately resistance to alternaria leaf blight, offering valuable genetic resources for enhancing linseed resilience to this disease through breeding initiatives.